Quality assessment of some baryte ores in Benue state area, Nigeria for oilfield drilling - Debrah Memshima Oahimire; Victor Uchechi Ukaegbu; Joel Friday Ogbonna (Journal of Degraded and Mining Lands Management, 2021)
The massive exploration and production well drillings in Nigerian oilfield indicate the demand for drilling fluid supplements such as baryte, in managing over-pressured formations and preventing hazardous blowouts. The underdevelopment of Nigerian solid minerals has created a wide gap between the demand and supply of the local resource, whereas there exist some assertions that the Nigerian baryte quality is below the American Petroleum Institute, API, standard. This study aimed at testing and evaluating qualitatively, based on API standards, some baryte ores from the Benue area, Nigeria, to establish their usefulness or otherwise in oilfield drilling operations. General field studies and sampling with laboratory studies were done including flame tests, X-ray Diffraction and X-ray fluorescence, to confirm mineralogy and chemical compositions of the barytes respectively and very importantly, the API tests prescribed for drilling grade barytes were carried out. The results showed impressive quality barytes with a specific gravity range from 4.10 to 4.49 and concentration of alkaline earth metals as calcium, Ca, 20mg/kg to 48mg/kg, particle sizes processed within API standard requirement, and the weight percentage of BaSO4 composition of the ores ranged from 93.55% to 99.61%.  There were no significant impurities of threat such as carbonates, iron ores, silicates and sulphides. The estimation of reserves and proper development of the resource is highly recommended as the quantity and quality might enhance the sustainability of local drilling grade baryte supply and save Nigeria the current huge capital flight and other plights